Association between metabolically healthy central obesity in women and levels of soluble receptor for advanced glycation end products, soluble vascular adhesion protein-1, and activity of semicarbazide-sensitive amine oxidase - Volkovova, Katarina; Szoko, Eva; Csongova, Melinda; Sebekova, Katarina; Koborova, Ivana; Gurecka, Radana; Tabi, Tamas (Croatian medical journal, 2017)
To determine the levels of circulating soluble receptor for advanced glycation end products (sRAGE), as a biomarker of risk of metabolic syndrome and cardiovascular disease development in centrally obese (CO) women considered metabolically healthy (COH) in comparison with those metabolically unhealthy (COU). 47 lean healthy, 17 COH (presenting waist-to-height ratio ≥0.5 but not elevated blood pressure, atherogenic lipid profile, and insulin resistance), and 50 COU (CO presenting ≥2 risk factors) women aged 40-45 years were included. Anthropometric characteristics, blood chemistry and hematology data, adipokines, markers of inflammation, sRAGE, soluble vascular adhesion protein-1 (sVAP-1), and the activity of semicarbazide sensitive amine oxidase (SSAO) were determined. Central obesity associated with low sRAGE levels (lean healthy: 1503±633 pg/mL; COH: 1103±339 pg/mL, P<0.05; COU: 1106±367 ng/mL, P<0.0.1), hyperleptinemia, and elevated markers of inflammation irrespective of the presence or absence of cardiometabolic risk factors. COU women presented high adiponectin levels. SVAP-1 concentrations and the activity of SSAO were similar in all 3 groups. COH women present abnormalities in non-standard markers of cardiometabolic risk (sRAGE, leptin, high sensitive C-reactive protein), supporting the view that there is no healthy pattern of obesity. The clinical impact of our findings for future prognosis of metabolically healthy obese subjects remains to be elucidated in longitudinal studies.